PENDIDIKAN POLITIK BAGI PEMILIH PEMULA: MEWUJUDKAN GENERASI CERDAS DAN BERTANGGUNG JAWAB DALAM DEMOKRASI - Rachmat Rachmat; Neli Yuliawati; Rio Afrizal Pratama (PT. ABIG RIZKY PUBLISHER, 2026)
This community service activity aims to enhance the political literacy, awareness, and participation of first-time voters through the theme “Political Education for First-Time Voters: Realizing a Smart and Responsible Generation in Democracy”. The initiative is driven by the relatively low levels of political literacy among the youth and the growing challenges of hoaxes and disinformation in the digital era. The program was conducted at SMK PGRI Takokak on January 29, 2026, involving 50 twelfth-grade students and facilitated by lecturers from STISIP Guna Nusantara Cianjur. The methods employed included interactive lectures, group discussions, case studies on actual phenomena such as money politics and hoaxes, and a direct simulation of the general election process. The results indicate a significant increase in students' understanding of basic democratic concepts and their strategic role as citizens. Furthermore, students demonstrated improved critical thinking skills in filtering political information on social media. The election simulation provided practical experience that reinforced values of integrity and responsibility. In conclusion, this educational-participatory approach is effective in cultivating smart and critical first-time voters, which is essential for maintaining the quality of democracy in Indonesia.